Impacts of Warming and Acidification on Coral Calcification Linked to Photosymbiont Loss and Deregulation of Calcifying Fluid pH - Louise P. Cameron; Claire E. Reymond; Jelle Bijma; Janina V. Büscher; Dirk De Beer; Maxence Guillermic; Robert A. Eagle; John Gunnell; Fiona Müller-Lundin; Gertraud M. Schmidt-Grieb; Isaac Westfield; Hildegard Westphal; et al. (Journal of Marine Science and Engineering, 2022)
Corals are globally important calcifiers that exhibit complex responses to anthropogenic warming and acidification. Although coral calcification is supported by high seawater pH, photosynthesis by the algal symbionts of zooxanthellate corals can be promoted by elevated pCO2. To investigate the mechanisms underlying corals’ complex responses to global change, three species of tropical zooxanthellate corals (Stylophora pistillata, Pocillopora damicornis, and Seriatopora hystrix) and one species of asymbiotic cold-water coral (Desmophyllum pertusum, syn. Lophelia pertusa) were cultured under a range of ocean acidification and warming scenarios. Under control temperatures, all tropical species exhibited increased calcification rates in response to increasing pCO2. However, the tropical species’ response to increasing pCO2 flattened when they lost symbionts (i.e., bleached) under the high-temperature treatments—suggesting that the loss of symbionts neutralized the benefit of increased pCO2 on calcification rate. Notably, the cold-water species that lacks symbionts exhibited a negative calcification response to increasing pCO2, although this negative response was partially ameliorated under elevated temperature. All four species elevated their calcifying fluid pH relative to seawater pH under all pCO2 treatments, and the magnitude of this offset (Δ[H+]) increased with increasing pCO2. Furthermore, calcifying fluid pH decreased along with symbiont abundance under thermal stress for the one species in which calcifying fluid pH was measured under both temperature treatments. This observation suggests a mechanistic link between photosymbiont loss (‘bleaching’) and impairment of zooxanthellate corals’ ability to elevate calcifying fluid pH in support of calcification under heat stress. This study supports the assertion that thermally induced loss of photosymbionts impairs tropical zooxanthellate corals’ ability to cope with CO2-induced ocean acidification.